1981
DOI: 10.1111/j.1365-2885.1981.tb00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Emetic action of xylazine on the chemoreceptor trigger zone for vomiting in cats

Abstract: Xylazine is an effective sedative analgesic that induces vomiting in the cat. A consistently effective intramuscular emetic dose of xylazine was established in normal cats in this laboratory. Animals in which the area postrema of the medulla oblongata had been chronically destroyed did not exhibit emesis in response to the standard test dose of xylazine but continued to show sedation. By contrast, sham-operated cats responded normally. Refractoriness to deslanoside, a known specific emetic drug, was used as fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 3 publications
5
39
1
Order By: Relevance
“…The results of this study confirm a chemoreceptive function of AP for xylazine-induced vomiting in cats (Colby et al 1981). In addition, a chemoreceptive function for the AP in the production of pharmacologically induced CTA is indicated for both monkeys and cats.…”
Section: Discussionsupporting
confidence: 70%
“…The results of this study confirm a chemoreceptive function of AP for xylazine-induced vomiting in cats (Colby et al 1981). In addition, a chemoreceptive function for the AP in the production of pharmacologically induced CTA is indicated for both monkeys and cats.…”
Section: Discussionsupporting
confidence: 70%
“…The initial decrease followed by an increase in PaO 2 in the XK and DK groups was attributed to the short lasting depressant effect of ketamine (Wright, 1982). Colby et al (1981) reported a decrease of 23% in PaO 2 in cats with XK combination. Diazepam decreased PaO 2 insignificantly but when it was supplemented with ketamine, it produced a short decrease in PaO 2 (Haskins et al, 1986).…”
Section: Discussionmentioning
confidence: 96%
“…Briefly, each animal was fasted overnight and fed 150 g of commercial canned food on the day of the experiment, and then xylazine (0.66 mg/kg IM) was injected to induce vomiting 1 h later. The dosage was selected because it was the effective dose to induce emesis in 95% of cats injected with xylazine (12,13). Cats then were observed for 30 min to enable us to assess the vomiting variables.…”
Section: Methodsmentioning
confidence: 99%